‘Why did he do it? Because he’s a Fucking Bloke’: victim Insights into the Perpetration of Street Harassment - Hindes, Sophie (The British journal of criminology, 2023)
Despite the pervasive nature of street harassment, there is currently little research exploring who perpetrates street harassment and why. Drawing on interviews with Australians who have experienced street harassment, we examine their insights into perpetration. Participants identified individual-level, social/cultural, structural and contextual factors that facilitate street harassment. While existing theoretical explanations of gendered violence help to account for the perpetration of street harassment, these were not sufficient in accounting for participants’ experiences. Participants often drew on gendered, aged, classed and racial stereotypes in their perceptions of perpetrators. We argue that a nuanced understanding of power that accounts for multiple, intersecting forms of marginalisation is needed to understand who perpetrates, as well as who is perceived to perpetrate street harassment.